The Effect of Laboratory Practical Activities on Senior High School Student's Academic Performance in Relation to Force Concept - Owusu, Gideon (International Journal of Education, Culture, and Society, 2023)
The problem of solving questions related to force faced by form two science students of St. James Seminary/Senior High School was an issue which led to this study. The problem of students' negative attitudes toward learning about force and their poor performance in force concepts was discovered through direct observation in the school setting. Students have shown difficulties understanding the concepts of force because they have difficulties with the kind of abstract thinking used by scientists. Additionally, because of the language that is used in our environment on a daily basis and since scientific terminology frequently differs from that of common speech, students usually have ideas that are different from those of scientists. It is commonly thought that teaching and understanding the concept of force, particularly when it involves acceleration, is difficult. To curb the problem identified, laboratory practical activities was employed. Sixty-two second year students of St. James Seminary/Senior High School in the Sunyani Municipality in Bono Region were purposively sampled into experimental and control groups. The experimental group was taught using laboratory practical activities as instructional technique and the control group using traditional method of teaching. Two research questions and a hypothesis were raised in the study. The instruments were pre-test and post-test, practical activities, observation and questionnaires for both the experimental and control groups. Data collected were analysed using simple frequency, z-test and descriptive statistics. The findings revealed that students exposed to frequent laboratory practical activities performed better than those exposed to traditional method of teaching. The findings from the research also indicated that students in the experimental group confidence increased from lesson to lesson. The study recommends that physics teachers take students through a lot of more laboratory practical activities, since this will help students’ gain better understanding of the concept and improve their academic performance.